Growth and risk of adverse neuro‐developmental outcome in infants with congenital heart disease: A systematic review. (14th October 2022) - Trivedi, Amit; Browning Carmo, Kathryn; Jatana, Vishal; James‐Nunez, Kristen; Gordon, Adrienne
Abstract: Aim: Congenital heart disease (CHD) is one of the most common birth defects affecting around 1:100 infants. In this systematic review, we aimed to determine impact of growth on neurodevelopmental outcomes of infants with CHD. Methods: Studies that reported association of growth with developmental outcomes in infants with CHD who had surgery, were included. The search strategy was prospectively registered. Relevant studies were identified by electronic searches. The Cochrane Central Register of Controlled Trials, MEDLINE and EMBASE were searched from their earliest date to February 2022. Results: Twenty studies met inclusion criteria. Choice of growth measures, developmental assessment tools and timing of assessment varied widely precluding conduct of a meta‐analysis. Seventeen studies reported on infants who had cardio‐pulmonary bypass. Birth weight was reported in thirteen studies and was associated with adverse outcome in nine. Head circumference at birth and later predicted developmental outcomes in five. Impaired postnatal growth was associated with adverse developmental outcome in seven studies. Conclusion: Growth in infants with congenital heart disease, specifically single ventricle physiology can predict adverse neurodevelopmental outcome. Included studies showed significant clinical heterogeneity. Uniformity should be agreed by various data registries with routine prospective collection of growth and developmental data.